Teacher-Mediated Pronunciation Instruction: Its Effects on Enhancing the Oral Language Fluency of Seventh-Grade English Students - Barrun, Jason S.; Sia, Jonald B. (Future Science / FSH-PH Publications, 2023)
This study investigated the effects of teacher-mediated pronunciation instruction on enhancing the oral language fluency of seventh-grade English students. Using a quasi-experimental pretest-posttest non-equivalent groups design, 32 learners served as respondents of the thirteen-session- study in a secondary school in Southern Luzon, Philippines. The student-respondents were tested to find out whether there would be a significant difference in their knowledge and application of the segmentals and suprasegmentals before and after the implementation of the said intervention. In all the instruments, namely the dictation test, pronunciation achievement test, and aural-oral achievement test, the findings revealed that the experimental group performed significantly higher than the control group. Through the independent sample t-test and Analysis of Covariance (ANCOVA), the results revealed that the experimental group had higher mean scores than the control group with t-computed values exceeding the tabular values affirming that an explicit pronunciation instruction is better in enhancing the oral language fluency of students than only incidental acquisition. The more the learners are exposed to an intervention, the more that they will become intelligible. Other effects also include the more frequently that the teacher conducts various games, the more that the students enjoy and learn pronunciation; and the more refined a learner’s pronunciation skill is, the more improved he/she is when it comes to listening comprehension and spelling. Finally, it is recommended that more and newer interventions regarding second language phonology or any content that focuses on speaking as a macro-strand in English should be delved into.